Research on the Relationship between the Growth of OTT Service Market and the Change in the Structure of the Pay-TV Market - Sungwook Park; Youngsun Kwon (International Telecommunications Society (ITS), 2019)
Over-the-top media firms such as Netflix, Amazon Prime, and Hulu are transforming the coopetition relationship among media firms in the broadcasting market and the structure of the broadcasting industry. New entrants like OTT media firms kept using various coopetition strategies including mergers and acquisitions in order to gain a foothold in the firmly entrenched broadcasting industry. A few OTT media firms already successfully made inroads into the media industry and are expanding their turf in many countries, triggering drastic changes in the structure of the broadcasting industry. The entry of OTT firms has also been increasing tension with fixed and mobile broadband network operators worldwide and induced NOs to become OTT media firms themselves. In this paper, we propose an empirical study on the major countries with large broadcasting market size. This paper shows that OTT services in major countries having the huge TV market commonly use "localization strategy", "partnership strategy", "content differentiation strategy", "revenue enhancement strategy", and "service optimization strategy". Add to these strategies, pay-TV incumbents use "envelopment strategy" and "diversification strategy" as well. In addition, OTT service revenues and fixed broadband subscriptions by major countries are set as independent variables, and the herfindahl-hirschman index of pay-TV market, which measures the market concentration, and the ratio of households subscribing to pay-TV services by major countries are set as dependent variables. Considering different characteristics of broadcasting market of each country, public funding, subscription revenue, advertising revenue, IPTV, satellite broadcasting platform, and cable broadcasting platform are set as dummy variables for applying the least square dummy variable analysis. As a result, it turns out that the increase in fixed broadband subscriptions has a statistically significant impact on the increase in the pay-TV market concentration and the cord-cutting phenomenon, but OTT service revenues do not affect.
Keywords: 330; OTT; Broadcasting industry; Media Coopetition; Catfish effect